Implementation of the Two Stay, Two Stray Cooperative Learning Model in Islamic Education - Tegar Elyanda; Subardi; Muhammad Insan Jauhari (Smart Edu Center, 2026)
The learning process in Islamic Religious Education (PAI) at the elementary school level is often dominated by conventional teacher-centered methods, resulting in unequal student participation, limited interaction, and low collaborative engagement. This condition necessitates the implementation of innovative learning approaches that encourage active student involvement. Therefore, this study aimed to describe the implementation of the Two Stay Two Stray (TSTS) cooperative learning model in Islamic Religious Education at SD Negeri 11 Sijuk and to explore how the model promotes collaborative and interactive learning. This study employed a qualitative descriptive approach. The participants consisted of one Islamic Religious Education teacher and 24 sixth-grade students who were purposively selected due to their readiness to engage in cooperative learning activities. Data were collected through classroom observations, semi-structured interviews, and documentation. The collected data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the TSTS model was carried out through three interconnected stages: planning, implementation, and evaluation. During the planning stage, the teacher prepared instructional modules and formed heterogeneous groups. During implementation, students actively exchanged information through structured “stay” and “stray” roles, while teacher scaffolding and class agreements ensured orderly participation. In the evaluation stage, authentic assessment was used to monitor students’ understanding, communication skills, collaboration, and engagement. The model successfully increased student participation, fostered peer interaction, and promoted the development of social and Islamic character values such as responsibility, respect, and cooperation. The TSTS cooperative learning model provides an effective framework for creating active, collaborative, and character-oriented Islamic Religious Education learning environments in elementary schools